Feedback effects in the relationship between the built environment and travel. - Maat, Kees; Arentze, Theo (Routledge, 2012)
Clearly, the built environment has certain effects on the travel behavior of individuals and households, but Dutch research findings indicate that this relationship is quite complex. Although the argumentation behind these spatial concepts sounds plausible, other mechanisms may complicate the relationship between travel behavior and the built environment. Rather than the built environment having a straightforward influence on trip frequencies, travel distances and mode choices, we may be dealing with endogenous relationships, in which individuals take into account other preferences, other activities and travel, other people, and other locations. The goal of this study is to review primarily Dutch empirical work that goes beyond direct associations and address these feedback effects in the relationship between the built environment and travel behavior. It is argued that second order effects, such as rebound effects and residential self-selection are largely responsible for this.
Keywords: Raumplanung; Raumstruktur; Verkehrsverhalten; Infrastruktur; Verkehrsmittelwahl; Mobilitätsverhalten